2018
DOI: 10.1136/bmj.k4986
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up primary health services for improving reproductive, maternal, and child health: a multisectoral collaboration in the conflict setting of Afghanistan

Abstract: Jai Das and colleagues present an innovative and evolutionary model of multistakeholder and multisectoral collaboration in scaling up coverage of health services in Afghanistan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 20 publications
(33 reference statements)
1
21
1
Order By: Relevance
“…These findings are not surprising as other studies have also reported on stagnant contraception rate and decreasing ANC and vaccination rates [2,16]. A study reported low coverage of RMNCAH&N services among less wealthy households and stated that only half of the women were benefiting from it [2]. The study also showed that conflict significantly impacted health service delivery, as the coverage of most RMNCAH&N services through the continuum of care was significantly lower in provinces which had ongoing conflict and insecurity compared to provinces which were relatively free of conflict.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…These findings are not surprising as other studies have also reported on stagnant contraception rate and decreasing ANC and vaccination rates [2,16]. A study reported low coverage of RMNCAH&N services among less wealthy households and stated that only half of the women were benefiting from it [2]. The study also showed that conflict significantly impacted health service delivery, as the coverage of most RMNCAH&N services through the continuum of care was significantly lower in provinces which had ongoing conflict and insecurity compared to provinces which were relatively free of conflict.…”
Section: Discussionsupporting
confidence: 75%
“…The stagnant coverage of the use of contraceptives can also be linked to cultural norms, insecurity, illiteracy among women and socio-economic status of the people. These findings are not surprising as other studies have also reported on stagnant contraception rate and decreasing ANC and vaccination rates [2,16]. A study reported low coverage of RMNCAH&N services among less wealthy households and stated that only half of the women were benefiting from it [2].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In the remaining three provinces, health services are provided directly by the Afghan government, under the Strengthening Mechanism Project [6].…”
Section: Introductionmentioning
confidence: 99%